A velhice no estatuto do idoso - Rozendo, Adriano da Silva [UNESP]; Justo, José Sterza [UNESP] (My University, 2010)
The “Estatuto do Idoso”, is a low created from arrangements about seniors citizens contained in the “Constitution of 1988”, assumes a substantial function in the way that the old age is seen and treated in the Brazilian society. This article, a resulted from a research made by the actual researchers, had how analyses’ objective the content of the “Estatuto”, trying to identify images and senses attributed to the old age, with which the senior’s figure have been built, like a differentiated figure. Was possible to apprehend in the “Estatuto” the attempt of differentiating the seniors like citizens of rights, marked by own characteristics who demand protections, services and special benefits. However, a critical examination of the preoccupation, supports, and protection contained in the “Estatuto” allows understanding that the senior finishes being built like fragile, impotent and incompetent being to assuming the management of them lives.

O Estatuto do Idoso, criado como decreto-lei a partir de disposições sobre o idoso contidas na Constituição de 1988, assume um papel fundamental na maneira como a velhice é vista e tratada na sociedade brasileira. Este artigo, resultado de uma pesquisa realizada pelos próprios pesquisadores, teve como objetivo analisar o conteúdo do Estatuto, procurando identificar imagens e sentidos básicos atribuídos à velhice, com os quais se constrói a figura do idoso, como uma figura diferenciada, e se definem práticas, especialidades, espaços próprios, e tecnologias de gestão do envelhecimento. Foi possível apreender no Estatuto a tentativa de diferenciar os idosos como cidadãos de direitos, marcados por características próprias que demandam proteções, serviços e benefícios especiais. No entanto, um exame crítico das preocupações, amparos e proteções estatutárias permite entender que o idoso acaba sendo construído como um ser frágil, limitado, impotente e incapaz de assumir a gestão da própria vida.
The old age in Estatuto do Idoso
Keywords: Old age; Seniors citizens; Senses; Estatuto do Idoso; Velhice; Terceira idade; Sentidos